Pendidikan Keluarga dalam Perspektif Islam: PENDIDIKAN KELUARGA DALAM PERSPEKTIF ISLAM - Ubabuddin, Ubabuddin (Ali Muchasan, 2018)
First and foremost children's education in the family must be based on the corridor of Islam by holding on to the Qur'an and Sunnah of the Prophet. Education in the family is based on the guidance of the Islamic religion intended to form children in order to be faithful and devoted to Allah SWT, as well as being noble that includes ethics, morals, manners, spiritual or understanding and experience of religious values ​​in daily life. This is a manifestation of the life of ‘amar makruf nahi munkar’ in family life, namely by giving education to his sons and daughters based on Islamic teachings. Children as a mandate given by Allah to their parents certainly need guidance based on the guidance of the Islamic religion which is taught in the family environment towards maturity. The pattern or method of religious education in Islam basically follows the behavior of the Prophet Muhammad SAW in fostering his family and friends. Because all that is done by the Prophet Muhammad is a manifestation of the content of the Qur'an.